Measuring the linear viscoelastic regime of MCF-7 cells with a monolayer rheometer in the presence of microtubule-active anti-cancer drugs at high concentrations - Lee, Suhyang; Bashir, Khawaja Muhammad Imran; Jung, Dong Hee; Basu, Santanu Kumar; Seo, Gayeon; Cho, Man-Gi; Wierschem, Andreas (Interface Focus, 2022)
The rheological properties of cells have vital functional implications. Depending, for instance, on the life cycle, cells show large cell-to-cell variations making it cumbersome to quantify average viscoelastic properties of cells by single-cell techniques. Microfluidic devices, typically working in the nonlinear viscoelastic range, allow fast analysis of single-cell deformation. Averaging over a large number of cells can also be achieved by studying them in a monolayer between rheometer discs. This technique allows applying well-established rheological standard procedures to cell rheology. It offers further advantages like studying cells in the linear viscoelastic range while quantifying cell vitality. Here, we study the applicability of the technique to rather adverse conditions, like for microtubule-active anti-cancer drugs and for a cell line with large size variation. We found a strong impact of the gap width and of normal forces on the moduli and obtained high vitality levels during the rheological study. To enable studying the impact of microtubule-active drugs on vital cells at concentrations several orders of magnitude beyond the half maximal effective concentration for cytotoxicity, we arrested the cell cycle with hydroxyurea. Irrespective of the high concentrations, we observed no clear impact of the microtubule-active drugs.
CRIS-Team WoS Importer:2022-11-04